2004
DOI: 10.1210/me.2003-0380
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Transcription of the ADAMTS-1 Gene by Luteinizing Hormone and Progesterone Receptor

Abstract: ADAMTS-1 (a disintegrin and metalloproteinase with thrombospondin-like motifs) is a multifunctional protease that is expressed in periovulatory follicles. Herein we show that induction of ADAMTS-1 message in vivo and transcription of the ADAMTS-1 promoter in cultured granulosa cells are dependent on separable but coordinate actions of LH and the progesterone receptor (PR). To analyze the molecular mechanisms by which LH and PR regulate this gene, truncations and site-specific mutants of ADAMTS-1 promoter-lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 51 publications
9
88
1
5
Order By: Relevance
“…2: lanes 2 and 3), FOXOA3 alone had negligible activity, but the addition of the ligand R5020 caused a slight increase in the luciferase activity, suggesting that COS cells have a factor that not only recognizes a GRE but also responds more strongly in the presence of FOXOA3. Transfection of PGRA dramatically induced ligand-dependent, but not ligand-independent, promoter activity (lane 4 compared with lane 1), confirming earlier observations (Zhao et al 2001, Doyle et al 2004. Moreover, when increasing amounts of FOXOA3 were co-expressed with PGRA, each Figure 1 Schematic of FOXO constructs and activity on an IRS-driven promoter.…”
Section: Foxo1a and Pgra Functionally Interact On A Pgrresponsive Prosupporting
confidence: 82%
See 1 more Smart Citation
“…2: lanes 2 and 3), FOXOA3 alone had negligible activity, but the addition of the ligand R5020 caused a slight increase in the luciferase activity, suggesting that COS cells have a factor that not only recognizes a GRE but also responds more strongly in the presence of FOXOA3. Transfection of PGRA dramatically induced ligand-dependent, but not ligand-independent, promoter activity (lane 4 compared with lane 1), confirming earlier observations (Zhao et al 2001, Doyle et al 2004. Moreover, when increasing amounts of FOXOA3 were co-expressed with PGRA, each Figure 1 Schematic of FOXO constructs and activity on an IRS-driven promoter.…”
Section: Foxo1a and Pgra Functionally Interact On A Pgrresponsive Prosupporting
confidence: 82%
“…This may provide a molecular basis for the observed repressive effects of PGRA and ERS1 on the FOXO activation of an IRS promoter (data not shown; (Schuur et al 2001)). PGRA and ERS1 can act as co-regulatory molecules that enhance the functional activity of other transcription factors, such as SP1 and AP1 (McKenna & O'Malley 2002, Doyle et al 2004, Baron et al 2007 and references therein). Therefore, the cumulative effect of PGRA and FOXO1a on the complex Igfbp1 promoter may reflect the sum of these two opposing activities, positive actions of FOXOA3 with PGRA on the PRE site(s) and negative regulation of FOXOA3 on the IRS site.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone (PG) and its receptor (PR) are two genes that are activated by LH in ovaries. PG binds to receptors (PGR) on the granulosa cell resulting in increased ADAMTS1 (8,9,20,21) (Figure 2). In disorders of PR, which controls expression of ADAMTS1, ovulation and fertility problems are observed.…”
Section: Adamts In the Physiology Of Obstetrics And Gynecologymentioning
confidence: 99%
“…It has been reported that the proximal promoter region of the Tace/Adam17 gene has an SP-1 site and that the region plays an important role in the promoter activity [26], whereas a distinguishable consensus PGR response element (PRE) is not observed in the promoter region. Although Adamts-1 mRNA was expressed in a PGR-dependent manner in porcine cumulus cells [15] and murine granulosa cells [4], this promoter region also lacks PRE site [27]. Nevertheless, cotransfection of PGR expression vector enhanced Adamts-1 promoter activity via granulosa cell-rich SP-1/SP-3 binding sites [27].…”
Section: Discussionmentioning
confidence: 99%